Subtractive versus mass conserving metal shaping technologies: an environmental impact comparison. (15th January 2015) - Ingarao, Giuseppe; Priarone, Paolo C.; Gagliardi, Francesco; Di Lorenzo, Rosa; Settineri, Luca
Abstract: The scientific studies in the domain of environmental sustainability of metal processing technologies predominantly focus on conventional material removal processes, as milling and turning. Despite some exceptions, many other non-machining technologies, such as metal forming processes, are still not well documented in terms of their energy and resource efficiency. Moreover, to properly evaluate the environmental impact of a given process, a standing-alone approach is no longer sufficient. In order to offer a valuable contribution in the domain of metal shaping sustainability, the present paper proposes a thorough methodology entailing to compare, from the environmental point of view, two traditional technologies: a hot extrusion process (mass conserving approach) and a turning (subtractive) one. A Life Cycle Assessment (LCA) based approach is implemented to properly analyze the considered processes. An axi-symmetric aluminum component was selected to develop the analysis on. Besides the analysis of material flows occurring all along the life cycle of the component, the material use and the consumed electrical energy necessary for the tools manufacturing are measured to properly quantify the environmental impact of the production phases. The most relevant influencing factors within each technology are identified and quantified. Moreover, an analysis of the environmental performance of the two processes at the varying of the batch size is presented. The paper aims at providing some general guidelines for the identification of the greenest technology as the main influencing factors change. Highlights: Environmental comparative analyses of processes are becoming necessary. Metal forming processes are still not well studied in terms of environmental impact. Lack of systematic studies to identify environmental-friendly production strategies. Methods to select the greenest technology for varying product features are needed. LCA based methodology to compare a mass conserving approach and a subtractive one.